NOVEL LAKUNA KARYA KHRISNA PABICHARA: KAJIAN ANTROPOLOGI SASTRA - Kurnia Lindayani; Maria Matildis Banda; I Ketut Nama (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2023)
This research is entitled "Lakuna Novel by Khrisna Pabichara: Literary Anthropology Study". The novel Lakuna was analyzed because it contains many cultural elements. The aim of this research is to describe the structure of the novel and aspects of literary anthropology. The method used in this research is the analytical descriptive method, which is reading and analyzing the data that has been collected and then explaining it descriptively. In the structural analysis of the novel Lakuna, we found a description of the three elements that build the novel, those are plot, characterization and setting. The research results showed that the supporting additional characters. Several characters were described physically plot was divided into three stages, beginning, middle and the end. The plot in this novel used a linear plot. Characterization consists of main characters, supporting characters and,characteristikcally and socially. The setting was divided into three, they are the setting in the city of Makassar, afternoon time setting with the Bugis-Makassar socio-cultural background such as marriage customs, sirik customs, royal blood or caste, and traditional dances. In the anthropological aspect of literature, namely myths, customs and works of art. Myth. Aspects of the myth include being licked by the devil, ancestral curses, and cenning rara. Aspects of customs include sirik and makmanuk-manuk customs. Aspects of works of art include dances and pasinlirik art.